Multilocus genotyping of Giardia duodenalis (Lambl, 1859) from symptomatic human infections in Slovenia - Soba, Barbara; Islamovic, Sabina; Skvarc, Miha; Caccio, Simone M (Folia parasitologica, 2015)
Giardiasis is a common gastrointestinal infection of humans and animals with a worldwide distribution. Eight genetic groups (known as assemblages A to H) are currently recognised within the species complex of Giardia duodenalis (Lambl, 1859), of which assemblages A and B are responsible for infection of humans and other mammalian hosts. Genotyping data on giardiasis are not available from Slovenia. In this work, we have characterised isolates of G. duodenalis from 85 human symptomatic cases collected during 2002-2013. Genomic DNAs were first tested by a real-time (rt) PCR assay and then by conventional PCR at three loci (beta-giardin, bg; triose phosphate isomerase, tpi; and glutamate dehydrogenase, gdh). We found that the threshold cycle (Ct) values in rt-PCR testing were higher for samples collected during 2002-2005 and that this was paralleled by a low amplification rate in conventional PCR (6 of 32, i.e. 19%). In contrast, lower Ct values and higher amplification rate (45 of 53; 85%) were observed for samples collected during 2006-2013, suggesting an adverse effect of prolonged freezing of stools. Assemblages A and B were found with an almost identical frequency in the 51 genotyped samples. In agreement with previous studies, sequences from assemblage B isolates were characterised by larger genetic variability and by the presence of heterogeneous positions, which made assignment to specific genotypes difficult. Less variability was observed in sequences from assemblage A isolates, which belonged to the human-specific subassemblage AII. These data showed that the genotypes of G. duodenalis that circulate in humans in Slovenia are similar to those previously identified in Europe.
Keywords: dospělí; Genotype; Female; Adult; ženské pohlaví; Slovenia; lidé; Molecular Diagnostic Techniques; genotyp; Giardiasis; Phylogeny; Slovinsko; Male; diagnostické techniky molekulární; Genotyping Techniques; genotypizační techniky; giardiáza; Giardia lamblia; mužské pohlaví; fylogeneze; Humans